Ergonomic health hazards in selected secondary schools in the Enugu education zone, Nigeria - Ayuk, Martin Bate; Shalangwa, Angela Yusuf; Enebechi, Paul Chika (Orapuh Journal, 2020)
Introduction In educational ergonomics, a safe environment that supports teaching and learning activities or processes must be created in all schools. An unsafe teaching and learning environment may precipitate physical health conditions or injuries, impede the teaching or learning process, or restrict ideal activities among users. Purpose This study was aimed at examining ergonomic health hazards in selected secondary schools in the Enugu education zone of Enugu State, Nigeria. Materials and methods 327 teachers selected from a population of 1,800 through the purposive sampling technique were surveyed using a structured questionnaire named, ‘Teachers Ergonomic Health Hazard Questionnaire’ (TEHHQ). Data were analyzed using mean and standard deviation. The z-test statistic was used to test the hypothesis at the 0.05 level of significance. Results The study revealed that the majority of the buildings and teaching and learning facilities were in unsafe conditions in ergonomic terms (x̅ = 2.46, SD = 0.66). The study also revealed that the safety provisions were inadequate ( x̅ = 2.53, SD = 0.73) and there was a gross lack of regular maintenance of facilities and infrastructure in many secondary schools, which accounted for their poor states (x̅ = 2.40, SD = 0.59). There was no significant difference between the mean scores of male and female teachers on the ergonomic safety of school buildings and teaching-learning facilities (zcal = 1.32, ztab = 1.96), whereas the difference in the mean ratings of urban and rural secondary schools teachers on ergonomic health hazards, based on location was significant (zcal = 29.58, ztab = 1.96). Conclusion There is a need to engage best practices in the (future) structural and functional design and construction of the school environment to meet the comfort and health demands of users.